Uma Resenha - Heat, Greed and Human Need: climate change, capitalism and sustainable wellbeing (SER Social, 2023)
Resenha do livro "Heat, Greed and Human Need: climate change, capitalism and sustainable wellbeing", do autor Ian Gough, publicado originalmente em inglês, em 2017.